Heterogeneous responses and resistant mechanisms to crizotinib in ALK‐positive advanced non‐small cell lung cancer. Issue 9 (6th July 2018) - Kang, Jin; Chen, Hua‐Jun; Zhang, Xu‐Chao; Su, Jian; Zhou, Qing; Tu, Hai‐Yan; Wang, Zhen; Wang, Bin‐Chao; Zhong, Wen‐Zhao; Yang, Xue‐Ning; Chen, Zhi‐Hong; Ding, Yan; et al.
Abstract : Background: ALK‐tyrosine kinase inhibitors (TKIs) have been proven effective for treating ALK ‐positive non‐small cell lung cancer (NSCLC), although patients present with variable responses and disease progression courses. The detailed underlying molecular mechanisms require further investigation to yield a better prognosis. Methods: Targeted next‐generation sequencing (NGS) mutation profiling was performed on samples from 42 NSCLC patients confirmed positive for ALK rearrangements by fluorescence in situ hybridization or immunohistochemistry who experienced disease progression after crizotinib treatment. Results: ALK rearrangements were not confirmed in six patients (14%) with other potential oncogenic drivers identified by NGS, who therefore did not respond to crizotinib and had significantly shorter overall survival (OS) compared to NGS ALK ‐positive patients. Fifteen ALK activating mutations were detected in 8 out of 26 post‐treatment samples (31%), among which ALK L1196M and G1269A were the most common acquired mutations detected in half of the patients with ALK activating mutations. Dynamic monitoring of the genetic evolution in one patient revealed both spatial and temporal heterogeneity of resistant mechanisms during different ALK‐TKI treatment courses. Activation of ALK downstream or bypass pathways was detected in patients without ALK activating mutations, such as genetic alterations in PIK3CA, MET, and KRAS . Interestingly, we identified two patients with acquired mutations in the DNA mismatch repair gene POLE, which resulted in a dramatically increased tumor mutation burden, and might contribute to the poor response to crizotinib. Conclusions: Heterogeneous resistant mechanisms have been identified and correlate to diverse responses to crizotinib. Comprehensive and dynamic mutation profiling is required to better predict clinical outcomes.